It's all your fault - Rudnick, Paul (Scholastic Press, 2016)
Seventeen-year-old Caitlin Singleberry is a proper Christian teenager and member of a family singing group, but today she has been given a truly impossible assignment--keep her cousin Heller Harrigan, Hollywood wild child, out of trouble for the last weekend before her first big movie debuts.